2022
DOI: 10.1111/den.14459
|View full text |Cite
|
Sign up to set email alerts
|

Temporary sutures using reopenable clips and barbed threads

Abstract: BRIEF EXPLANATIONC LOSING A LARGE mucosal defect after endoscopic submucosal dissection (ESD) using an endoclip is a challenge. However, the closure of the mucosal defect is desirable to prevent post-ESD bleeding. 1,2 We developed a temporary suture method using reopenable clips and barbed threads.We used the SB Clip (SB-KAWASUMI, Tokyo, Japan) and SureClip (Micro-Tech Endoscopy, Nanjing, China) as the reopenable clips together with STRATAFIX Symmetric PDS Plus (Ethicon, Bridgewater, NJ, USA) as the barbed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…We have previously reported that the use of the E ndoscopist & A ssistant's S imulator dr Y lab (EASY; Tanac Co. Ltd., Gifu, Japan) ( Fig. 1 ) was useful in recruiting residents 1 . The version of EASY described in this report (EASY CSP) is an endoscopic simulator for resection by snare and clip closure developed by Matsuzaki and Tsunemi ( Fig.…”
Section: Endoscopy E-videosmentioning
confidence: 99%
“…We have previously reported that the use of the E ndoscopist & A ssistant's S imulator dr Y lab (EASY; Tanac Co. Ltd., Gifu, Japan) ( Fig. 1 ) was useful in recruiting residents 1 . The version of EASY described in this report (EASY CSP) is an endoscopic simulator for resection by snare and clip closure developed by Matsuzaki and Tsunemi ( Fig.…”
Section: Endoscopy E-videosmentioning
confidence: 99%